2020
DOI: 10.1111/jen.12765
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inbreeding in the early stages of artificially reared colonies of Bombus terrestris

Abstract: In the present study on the bumblebee Bombus terrestris, we investigated the influence of inbreeding on queen fitness by comparing diapause survival and egg‐laying success of queens mated with nestmate and non‐nestmate males. We then compared the early stage of colonies with or without diploid males and analysed colony characteristics to identify a factor predictive of colony outcome. Diapause survival was no different between queens mated with nestmates and non‐nestmates, but in the latter case, egg‐laying su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…Combining the genetic and productivity data in the B. hypnorum colonies reared from field-collected queens suggests that DMP decreased colony productivity (DMP colonies ( n = 5): mean n workers = 18, mean n gynes = 0, mean n males = 15; non-DMP colonies ( n = 32): mean n workers = 34, mean n gynes = 6, mean n males = 43). This suggestion is in line with previous findings in ants and bees [ 15 18 ], and exemplifies the fitness costs of matched matings in bumblebees. Such reductions in colony productivity may account for the lower DMP frequencies observed in mature, field-collected colonies than in queen-reared colonies ( figure 2 ), with smaller colonies being less likely to survive and be available for sampling, and support the assumption of sampling and/or survival bias in estimating DMP frequencies from field-collected colonies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Combining the genetic and productivity data in the B. hypnorum colonies reared from field-collected queens suggests that DMP decreased colony productivity (DMP colonies ( n = 5): mean n workers = 18, mean n gynes = 0, mean n males = 15; non-DMP colonies ( n = 32): mean n workers = 34, mean n gynes = 6, mean n males = 43). This suggestion is in line with previous findings in ants and bees [ 15 18 ], and exemplifies the fitness costs of matched matings in bumblebees. Such reductions in colony productivity may account for the lower DMP frequencies observed in mature, field-collected colonies than in queen-reared colonies ( figure 2 ), with smaller colonies being less likely to survive and be available for sampling, and support the assumption of sampling and/or survival bias in estimating DMP frequencies from field-collected colonies.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, DMP reduces colony founding success and productivity in both ants and bumblebees (Bombus spp.) [15][16][17][18]. In addition, a high frequency of DMP represents a strong indicator of a genetic bottleneck [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…A certain degree of inbreeding, revealed by the presence of colonies with diploid males, has been found in some commercial bumblebee companies, resulting in a potential economic loss, as these colonies are often unsuitable for pollination (Maebe et al, 2014;Bortolotti et al, 2020). In these circumstances, geometric morphometrics with the support of a large database can represent a quick and inexpensive method for diploid male detection, which allows immediate identification and elimination of colonies producing diploid males.…”
Section: Discussionmentioning
confidence: 99%
“…In case of homozygosity at the sex locus, fertilized eggs develop into diploid males instead (G€ osterit, 2016), decreasing the worker force and the number of gynes. For this reason, the production of diploid males decreases colony growth, which represents a serious disadvantage for the colony itself and the entire population (Zayed & Packer, 2005;Bogo et al, 2018a;Bortolotti et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Relatively low survival in gynes mated with related males during diapause was also observed (U. Gerloff and Schmid-Hempel 2005). However, it was found that diapause survival did not differ between gynes mated with siblings and those mated with nonsibling males (Bortolotti et al 2020). Inbreeding was also demonstrated to affect colony initiation, colony development, and queen fecundity (Gosterit 2016;Whitehorn et al 2009a).…”
Section: Introductionmentioning
confidence: 96%